National Juvenile Court Data Archive, United States, 1985-2019 - Sickmund, Melissa ([Verlag nicht ermittelbar], 2022)
The National Juvenile Court Data Archive houses over 15 million automated records of cases handled by courts with juvenile jurisdiction. Although some states' data contain traffic and dependency cases, the majority are delinquency and status offense records. The collection itself dates back to the 1920s when it was under the Children's Bureau, however in 1974 the Office of Juvenile Justice and Delinquency Prevention (OJJDP), within the U.S. Department of Justice assumed responsibility for the work of promoting access to automated juvenile court data sets for juvenile justice research and policymaking efforts. The Archive contains the most detailed information available on juveniles involved in the juvenile justice system and on the activities of U.S. juvenile courts. The Archive houses a sizable collection of automated juvenile court data files that not only support the national estimates but also support the study of a wide range of national and subnational juvenile justice issues. Designed to facilitate research on the juvenile justice system, the Archive's data files are available to policy-makers, researchers, students, and the public. The data have been used to explore a broad range of topics, from investigating the effectiveness of juvenile court programs and examining policy developments in individual jurisdictions, to monitoring the impact of legislative changes, and guiding juvenile justice system reform.